A relação entre governança e eficiência econômica em cooperativas agropecuárias brasileiras - Souza Junior, Wagner Dantas de (2019)
Cooperatives are economic and social organizations have the function and objective to maximize the welfare of members. The creation of economic value in these organizations occurs through the generation and distribution of direct benefits, such as the balance from the exercise, and indirect, like the negotiation of prices in the market, technical assistance, logistics and storage, cooperative education for cooperate, among other factors. The efficiency in this type of society can be impaired by the influence which the governance is structured, as there are problems stemming from its diffuse property rights that require strategies of loyalty, investment and management adopted to mitigate them. Therefore, this research aimed to analyze the relation between governance and economic efficiency in Brazilian agricultural cooperatives. This is a research based on the positivist epistemological paradigm, which uses a deductive, applied, quantitative, descriptive and documentary method. It uses public financial reporting data from a sample of 35 cooperatives for the year 2017. The methods of analysis used were the Data Envelopment Analysis in the DEA BCC output oriented model, supported by the Friedman Test and the Spearman Correlation. The product of economic efficiency was apprised by the Economic Value Added indicator in three models. The inputs used were the number of employees, fixed assets, cost of the product sold and operating expenses (proxy for the governance expenses). Several results were obtained: first, the choice of the instrument of performance evaluation of aggregate economic value influences the result of the exercise in a different and statistically significant way; second that the cooperatives have efficiency levels in the calculated DEA models - in Model 1, two DMUs were 100% efficient (Coocafé and Integrada), in Model 2, eight DMUs were considered 100% efficient (Capal, Coagro, Frisia, Primato, Unitá , Cotrijuc, Cotrisal and Casul) and in Model 3, only one DMU was 100%, Primato; third, that there are companies considered benchmarks in the conjunction of factors of production - the main ones were the Integrated, Cotrijuc, Primato, Capal and Casul; fourth, that the calculated models suggest the presence of increasing returns to scale; fifth, that management goals can be extracted for each DMU to maximize its EVA - for example, in Model 1 the aim of operating expenses is the average reduction of 25% of the input value; and sixth, that there is some relation between governance and economic efficiency in Brazilian agricultural cooperatives; in Model 1 (Traditional EVA), a weak and positive relation between variables was found, but not statistically significant, in Models 2 and 3, unlike a strong and significant association between variables was evidenced. This means that in agricultural cooperatives, if evaluated from a purely economic perspective, it does not have its efficiency associated with its governance expenditures. However, if evaluated by an economic and social perspective, considering the direct and indirect benefits associated with the cooperative, it is verified the existence of this relation. The results contribute scientifically to the empirical evaluation of the relation between governance and efficiency; and socially, with managerial information for the management of these firms and for public managers to determine politics for the sector.